PENINGKATAN SIFAT MEKANIS BESI COR KELABU MELALUI PROSES TEMPERING - A. Noor Setyo HD; Sri Widodo (Universitas Tidar, 2018)
This study aims to determine the Hardness and Toughness of cast iron after undergoing a Tempering process with independent variables heating time and dependent Hardness, microstructure and toughness Impack. Quenching was carried out at temperatures of 7750C, 8000C and 8250C in cold water media, while Tempering was carried out at temperatures of 2000C, 3000C and 4000C with a holding time of 15 minutes. Vickers Hardness test results using